1994
DOI: 10.1021/ma00083a002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lithium Chloride on the "Living" Polymerization of tert-Butyl Methacrylate and Polymer Microstructure Using Monofunctional Initiators

Abstract: The effect of LiCl on the anionic polymerization of tert-butyl methacrylate (tBuMA) initiated with monofunctional alkali metal-based carbanionic species was investigated at -78 °C in THF. The propagation rate of the polymerization process was determined by gas chromatography and by gravimetry. It was found that, in the presence of LiCl in a molar ratio of 5 with respect to the initiator, the rate constant, k9, is 20 times lower than that in the absence of LiCl. The polymers and oligomers were analyzed by size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
1

Year Published

1999
1999
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 4 publications
4
37
0
1
Order By: Relevance
“…However, at LiCl/RLi molar ratios higher than 2, k p decreases as the LiCl content is increased. The same observation was reported by Varshney et al for the anionic polymerization of tBMA in presence of LiCl [96], the effect of LiCl being however more drastic in this case (Table 6). Müller et al [97] have suggested that a 1:1 adduct would coexist with a less active 2:1 adduct (Scheme 15) [95], which has been recently debated [94].…”
Section: Oligomer Chains Complexed With Ligandssupporting
confidence: 89%
See 1 more Smart Citation
“…However, at LiCl/RLi molar ratios higher than 2, k p decreases as the LiCl content is increased. The same observation was reported by Varshney et al for the anionic polymerization of tBMA in presence of LiCl [96], the effect of LiCl being however more drastic in this case (Table 6). Müller et al [97] have suggested that a 1:1 adduct would coexist with a less active 2:1 adduct (Scheme 15) [95], which has been recently debated [94].…”
Section: Oligomer Chains Complexed With Ligandssupporting
confidence: 89%
“…Indeed, the content of isotactic placements is increased by 10% when a threefold molar excess LiCl is added to RLi. [96] No effect is however observed in case of PMMA, which remains unexplained. LiCl leads to a decrease in chain polydispersity when MMA and tBMA are polymerized in THF at low temperatures, and the mechanism is apparently living.…”
Section: Oligomer Chains Complexed With Ligandsmentioning
confidence: 98%
“…Polymerization of tert-butylmethacrylate in THF at Ϫ78°C resulted in polymers with fairly broad (by the standards of anionic polymerization) molecular weight distributions 51 (M w /M n ϭ 1.3), making it difficult to resolve the SEC peaks corresponding to the star and arm. The chromatogram exhibited rather broad peaks, where the different polymeric species could not be separated easily.…”
Section: Bromomethylbenzene Route To Polymethacrylate Starsmentioning
confidence: 99%
“…LiCl can be used to control the polymerization reaction by avoiding undesirable side reactions and to reduce the molecular weight distribution as demonstrated in previous studies. 51,52 LiCl also has another effect: It reduces the rate of the linking reaction. [51][52][53][54][55] It is documented that in the case of PtBuMA, LiCl forms -type complexes with the living polymer chains, reducing the propagation rate by a factor of 20 when compared to the rate in its absence.…”
Section: Bromomethylbenzene Route To Polymethacrylate Starsmentioning
confidence: 99%
See 1 more Smart Citation